Public Policy and non-recognition of arbitral awards, a comparative approach - Samuel, Silsy Rachel (2023)
This thesis delves into the intricate topic surrounding the defense of enforcing FAA on the public policy pretext, examining its impact with respect to the utilisation of arbitration in international commercial disputes. The discussion here compares how courts in chosen jurisdictions, namely UK, India, France, and UAE, approach the public policy notion as an exemption to FAA enforcement. Additionally, I am also exploring the numerous facets of public policy influencing courts' interpretations and exploring the public policy execution within the perspective of the influential NYC.